Head injury serum markers for assessing response to trauma: Design of the HeadSMART study. (23rd February 2017) - Peters, Matthew E.; Rao, Vani; Bechtold, Kathleen T.; Roy, Durga; Sair, Haris I.; Leoutsakos, Jeannie-Marie; Diaz-Arrastia, Ramon; Stevens, Robert D.; Batty, D. Scott; Falk, Hayley; Fernandez, Christopher; Ofoche, Uju; et al.
ABSTRACT: Background : Accurate diagnosis and risk stratification of traumatic brain injury (TBI) at time of presentation remains a clinical challenge. The Head Injury Serum Markers for Assessing Response to Trauma study (HeadSMART) aims to examine blood-based biomarkers for diagnosing and determining prognosis in TBI. Methods : HeadSMART is a 6-month prospective cohort study comparing emergency department patients evaluated for TBI (exposure group) to (1) emergency department patients evaluated for traumatic injury without head trauma and (2) healthy persons. Study methods and characteristics of the first 300 exposure participants are discussed. Results : Of the first 300 participants in the exposure arm, 70% met the American Congress of Rehabilitation Medicine criteria for TBI, with the majority (80.1%) classified as mild TBI. The majority of subjects in the exposure arm had Glasgow Coma Scale scores of 13–15 (98.0%), normal head computed tomography (81.3%) and no prior history of concussion (71.7%). Conclusion : With systematic phenotyping, HeadSMART will facilitate diagnosis and risk-stratification of the heterogeneous group of individuals currently diagnosed with TBI.